Cross-method comparison for BRAF p.V600 mutation cfDNA testing in Melanoma: BRAFI study - Clara Mayo de las Casas; Eloisa Jantus-Lewintre; Sebastian Ortiz Reina; Ana Drozdowskyj; Pablo Cerezuela-Fuentes; Jose Luis Manzano; Pablo Ayala de Miguel; Ana Arance Fernandez; Miguel Angel Berciano-Guerrero; Almudena Garcia-Castaño; Teresa Puertolas; Guillermo Crespo; et al. (EJC Skin Cancer, 2025)
Background: BRAF p.V600 mutation is the most frequent molecular driver alteration in melanoma. Detection of BRAF mutations in circulating-free DNA (cfDNA) reflects the shedding of tumor DNA and offers a potential non-invasive biomarker for disease monitoring and prognosis. However, the lack of standardized methodologies and inter-assay variability hinders its clinical implementation. Methods: The sensitivity, agreement and concordance of seven BRAF mutation detection assays were assessed across four laboratories. BRAF p.V600 mutation in pretreatment plasma samples was analyzed in 51 patients diagnosed with advanced stage melanoma using two digital PCR-based assays (droplet digital PCR -ddPCR- Bio-Rad and microfluidic digital PCR -Absolute Q, ThermoFisher Scientific-), three RT-PCR based assays (Idylla®, Cobas®, PNA-Q-PCR) and two NGS based assays (Oncomine™ Pan-Cancer Cell-Free Assay and Illumina Platforms). Results: digital PCR-based assays and Cobas® exhibited the highest sensitivity (51.0 %), followed by NGS Illumina® (45.1 %), Oncomine NGS / PNA-Q-PCR (43.1 %) and Idylla® (37.2 %). Results of different techniques showed a moderate to strong agreement, except for the comparison of Cobas with Idylla that was poor (Kappa=0.57). There was near-perfect agreement on detection of BRAF mutation between both NGS platforms and the NGS Illumina® with PNA-Q-PCR (Kappa = 0.92). Concordance of the quantitative results in terms of mutant allele frequency was near-perfect between NGS Illumina and ddPCR Bio-Rad assays (ICC = 0.99). Conclusions: Our study demonstrates substantial agreement among multiple cfDNA BRAF mutation detection assays, particularly between NGS and digital PCR assays. These findings support the potential utility of different techniques for BRAF testing in cfDNA.